Literatur review: Faktor-faktor munculnya Baby Blues pada ibu Postpartum - Prastowo, Anugrah Cahyani; Ardani, Tristiadi Ardi (Maliki Interdisciplinary Journal, 2024)
Baby blues syndrome is one type of depression experienced by a postpartum woman, generally occurs in the first 2 weeks postpartum and tends to peak on the third to fourth day postpartum. Baby blues have an impact on both mother and baby. Mothers will feel sad and anxious that have an impact on confidence in caring for the baby and trying to isolate themselves from the baby and the environment can even lead to the idea of leaving the baby. The purpose of this study is to identify the results of previous research on factors that can cause the occurrence of baby blues in postpartum mothers. The method used is a literature review study using relevant literature sources from 2014-2023. The results found that there are internal factors that cause the baby blues, namely age, education, economy, employment, and primipara parity, as well as external factors that include the type of childbirth and family social support. But not all mothers who experience the baby blues are influenced by the same factors because each mother has different risk factors for the baby blues.